Hiccups for HIPCs? - Craig Burnside; Domenico Fanizza (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
In this paper we discuss monetary and fiscal policy issues facing heavily-indebted poor countries (HIPCs) who receive debt reduction via the enhanced HIPC initiative. This debt relief program is distinguished from previous ones by its conditionality: freed resources must be used for poverty reduction. We argue that (i) this conditionality limits the extent to which the initiative relaxes the government's lifetime budget constraint; (ii) depending on the response of monetary policy to an increase in social spending there could be a short-term increase in inflation in HIPC countries, and (iii) the keys to longrun fiscal sustainability in the HIPCs are significant fiscal reforms by their governments, and the effectiveness of their poverty reduction programs in raising Growth.
Keywords: E31; H63; O11; O23; 330; debt relief; HIPCs; conditionality; government budget constraint; Schuldenerlass; Finanzpolitik; Geldpolitik; Haushaltskonsolidierung; Entwicklungsländer